(untitled) (Historia, 2021)
The relations between the Ngqika chiefdom and the British government at the Cape, 1806-1836 The relations between the British government at the Cape and the Ngqika in the period 1806-1836 played a very important and even a decisive role in the course of events on the eastern Cape frontier. This article is a brief overview of this interaction. The Ngqika are part of the Xhosa society. The group is named after their leader Ngqika (1775-1829). Die verhouding tussen die Britse owerheid en die Ngqikastam het in die tydperk 1806-1836 ’n uiters belangrike en selfs deurslaggewende rol in die verloop van gebeure aan die Kaapse Oosgrens gespeel. In hierdie artikel word kortliks na die interaksie gekyk. Die Ngqika behoort tot die Xhosastamgroep en is vernoem na stamhoof Ngqika (1775-1829).